PELABELAN GRACEFUL SATU MODULO PADA BEBERAPA GRAF EULE - Isa Isa; Lucia Ratnasari (Jurnal Matematika, 2014)
ABSTRACT. A graph  with  edges is said to be one modulo  graceful graph () if there is a injective function from vertex set of graph  to  in such a way that  induces a function  from edge set of graph  to  defined as  is bijective.  In this Last Project, the following Euler graphs : n-polygonal snakes,  and  under certain conditions which admit one modulo  graceful labeling () are learned.